The Role of Pharmacists in Patient Counselling for OTC Medication in Jordan: A Cross-Section Study - Abu-Zaid, Ala'; Barakat, Muna; Al-Qudah, Rajaa; Abdalhafez, Amer (Jordan Journal of Pharmaceutical Sciences, 2021)
Background: Community pharmacists represent the easiest-to-access medical experts for drugs. They play a major part in educating and counselling patients, especially regarding over the counter (OTC) medications. Purpose: This study aims to explore the role of pharmacists in patient counselling for OTC medication in Aqaba, Jordan. Methods: A cross-sectional survey was conducted with community pharmacists in Aqaba. An online self-administered survey was launched for the study sample via a social media platform (i.e. WhatsApp). The responses were imported into the Statistical Package for the Social Sciences (SPSS) for statistical analysis. Results: About half of pharmacists started their counselling by asking about the patient’s history. More than 70% of pharmacists advised patients in terms of their dosage regimen, the proper indications for the OTC medication, and any possible food-drug interactions. However, approximately one-third of pharmacists suggested there were many challenges in the counselling process. These included limitations in counselling time, work overload, more patients than the pharmacist’s capacity and a lack of counselling area. Conclusion: This study illustrates that community pharmacists are highly committed to pursuing their pharmaceutical care role through proper counselling for OTC medication in Aqaba. Moreover, our study highlights some challenges that pharmacists could face, which may interfere with the efficacy and safety of the drugs they provide.